Toll Roads : Recent Trends in Private Participation - Silva, Gisele F. (World Bank, Washington, DC, 2012)
During the 1990s developing countries increasingly turned to the private sector for construction, management, and maintenance of toll roads. Between 1990 and 1999, US$61 billion of private investment was committed to 279 projects in 26 developing countries, comprising 34,369 kilometers of toll highways, bridges and tunnels. This Note analyzes the main trends in private participation in toll roads in developing countries using figures from the World Bank's Private Participation in Infrastructure Project Database.